2018
DOI: 10.1101/371716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Skull base invasive low-grade meningiomas, a distinct genetic subgroup: A microarray gene expression profile analysis

Abstract: Introduction: Meningioma is the most common adult primary brain tumor originating from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The genomic invasiveness might be another reason; some recently published studies found that even WHO grade I meningioma could show high invasive molecular behavior-like high-grade meningiomas, if they harbor specific genetic background. The tumor can cause severe edema (which indicated disruption of the arachnoid and pia), invasion to the brain, and easy recurrence, et al (38,39). This may explain the intraoperative ICA rupture case (type I, WHO grade I, Figure 3A).…”
Section: Surgical Outcomes Of Acmsmentioning
confidence: 99%
“…The genomic invasiveness might be another reason; some recently published studies found that even WHO grade I meningioma could show high invasive molecular behavior-like high-grade meningiomas, if they harbor specific genetic background. The tumor can cause severe edema (which indicated disruption of the arachnoid and pia), invasion to the brain, and easy recurrence, et al (38,39). This may explain the intraoperative ICA rupture case (type I, WHO grade I, Figure 3A).…”
Section: Surgical Outcomes Of Acmsmentioning
confidence: 99%